The healing and transformative potential of lucid dreaming for treating clinical depression - Sackwild, Lana; Stumbrys, Tadas (International journal of dream research, 2021)
Lucid dreamers, who become aware within their dreams that they are dreaming, are able to use this state of consciousness for self-exploration and self-development, including the possibilities of therapeutic work. Preliminary evidence suggests that lucid dreaming may contribute to mental health. This explanatory sequential mixed methods study explored the relationship between lucid dreaming and depression . One hundred sixty-three participants, mostly lucid dreamers and many of whom had experienced depression, completed a survey investigating the relationship between lucid dreams and depression. Six survey participants then took part in in-depth qualitative interviews to elucidate how experienced lucid dreamers, who had been previously diagnosed with or prescribed medication for depression , utilized their lucid dreams to purposefully and practically access and alleviate the crux of their depression in the past . Both quantitative and qualitative data support the idea that lucid dream work may be an effective treatment for mental health issues, including clinical depression. Three major themes that emerged from the qualitative interviews - self-exploration, creativity and empowerment, spiritual and transpersonal - illustrate possible mechanisms of healing and transformation in the lucid dream state. Future studies should explore the potentials of lucid dreaming treatment for depression within a clinical or therapeutic programme.
Gesehen am 03.11.2021